Metabolic Characteristics of Oxcarbazepine (®Trileptal) and their Beneficial Implications for Enzyme Induction and Drug Interactions - Johann W. Faigle; Guenter P. Menge (Behavioural Neurology)
Hepatic oxygenases of the cytochrome P-450 family play a major role in the clearance of various anti-epileptic drugs. These enzymes are susceptible both to induction and to inhibition. Phenytoin, carbamazepine (CBZ), primidone, and phenobarbitone, for instance, are potent enzyme inducers. Other drugs, such as chloramphenicol, propoxyphene, verapamil, and viloxazine, inhibit cytochrome P-450. Pharmacokinetic behaviour is thus often altered, especially in combined medication, so that the dosage has to be re-adjusted if an optimum therapeutic outcome is to be ensured. Oxcarbazepine (OXC) is a keto analogue of CBZ. In the human liver the keto group is readily reduced, and the resulting monohydroxy metabolite is cleared by glucuronidation. The two enzymes mediating these reactions, i.e. aldo-keto reductase and UDP-glucuronyltransferase, do not depend on cytochrome P-450. The monohydroxy metabolite is the major active substance in plasma. Its elimination is not enhanced by OXC. Moreover, OXC seems to have little effect on cytochrome P-450. Aldo-keto reductases and glucuronyltransferases are in general less sensitive to induction and inhibition than are P-450 dependent enzymes. On the whole, OXC possesses very little potential for metabolic drug interactions, and thus differs favourably from other anti-epileptic drugs.